Operating Expenes Problem-Solving Through Workforce and Process Analysis For a Rubber Manufacturing Plant In Bandung - Sontania, Mesli; Utama, Akbar Adhi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
High operational costs have had a major impact on Bandung's CV XYZ rubber production plant. Labor, specifically in the completed goods section, accounts for the largest portion of operational expenditures, costing Rp 377,190,000. A labor and process efficiency study is required in order to cut expenses. This study intends to evaluate the labor and process performance of CV XYZ's finished goods division and make recommendations for enhancements. CV XYZ has enough capacity, according to the capacity study, to satisfy current demand without going beyond. Small products are used 65.91% of the time, medium products 67.73%, and large products 53.81%. The efficiency rate for medium-sized products is 81.59%, large-sized products is 64.82%, and small-sized products is 79.41%. Waiting waste was identified as the most common process by a thorough process mapping. Eight workers were found to be under load, whereas one worker had a typical workload, according to the workload study. Reengineering business processes proposes integrating components or operations to better. During the rubber vulcanization process, the suggested method cuts down on worker idle time. The new workload distribution is computed using the re-engineered business process as a base. Even though it falls under the under-load category, this leads to fewer employees and a greater burden. By using this suggested method, CV XYZ can save Rp 125.730.000,00, or 33% of its direct labor expenditures